Fictions of the Female Self - Parkin-Gounelas, R. author. aut Link
IX, 203 p.
Keywords: Women's novels have traditionally been read as 'subjective'. Through an examination of three generations of women's fiction in the post-Romantic period, this book challenges traditional readings of women's novels and argues that fiction writing for women has often been a matter of self-erasure rather than self-inscription. In particular, it examines the changing strategies, sometimes collusive and sometimes rebellious, which Charlotte Bronte, Olive Schreiner and Katherine Mansfield employed in their tentative project of inscribing female subjectivity into the novel and story form.